Transition Wave in the Collapse of the San Saba Bridge - Brun, Michele; Giaccu, Gian Felice; Movchan, Alexander B.; Slepyan, Leonid I. (Frontiers in Materials, 2014)
A domino wave is a well-known illustration of a transition wave, which appears to reach a stable regime of propagation. Nature also provides spectacular cases of gravity driven transition waves at large scale, observed in snow avalanches and landslides. On a different scale, the micro-structure level interaction between different constituents of the macro-system may influence critical regimes leading to instabilities in avalanche-like flow systems. Most transition waves observed in systems such as bulletproof vests, racing helmets under impact, shock-wave driven fracture in solids, are transient. For some structured waveguides a transition wave may stabilize to achieve a steady regime. Here we show that the failure of a long bridge is also driven by a transition wave that may allow for steady-state regimes. The recent observation of a failure of the San Saba Bridge in Texas provides experimental evidence supporting an elegant theory based on the notion of transition failure wave. No one would think of an analogy between a snow avalanche and a collapsing bridge. Despite an apparent controversy of such a comparison, these two phenomena can both be described in the framework of a model of the dynamic gravity driven transition fault.